Front Cover: Noncovalent Spin‐Labeling of DNA and RNA Triplexes (C&B 2/2020). Issue 2 (28th January 2020) - Kamble, Nilesh; Wolfrum, Manpreet; Halbritter, Thomas; Sigurdsson, Snorri T.; Richert, Clemens
Abstract : Front Cover . Designed DNA and RNA triplexes may be spin‐labeled using the guanine derivative shown in the upper right‐hand corner of the cover graphic. The labeling does not require a covalent bond and is based on Watson‐Crick plus Hoogsteen base pairing of the guanine base and unpaired pyrimidines of the triplex. The resulting complexes have dissociation constants in the micromolar range, as reported by Kamble and Wolfrum et al . in their full paper at 10.1002/cbdv.201900676 .